Ovarian cysts in cattle : a review - Mimoune, Nora (Array, 2021)
Ovarian cysts (OC) are one of the major factors affecting the fertility of dairy cattle due to their negative effects on reproductive performances, causing great economic losses. They have been traditionally defined as anovulatory follicular structures with a diameter exceeding 20 or 25 mm, lasting at least 10 days on the ovary in the absence of a functional corpus luteum. However, in recent years, the development of ovarian ultrasound and hormonal assays, particularly progesterone (P4), have provided additional information, thus changing the definition of this disease. These methods were proposed as the most effective combination for the diagnosis of OC. Treatments are primarily based on the use of different hormones or hormonal associations. Particularly, the standard treatment is GnRH. PGF2α is very effective in the case of luteal cyst. However, treatment failures observed with commonly administered hormones require the use of second-line treatments. Therefore, the Ovsynch protocol and progestogen appear to be a possible alternative in OC treatment. In order to prevent OC formation and to reduce OC incidence, strategies should focus on reducing diseases and stress and optimizing food intake during dry-off and post-partum (PP) periods. Medical prevention has been proposed with the same substances commonly used in treatment (GnRH, PGF2α).